Structure-based identification of a new IAP-targeting compound that induces cancer cell death inducing NF-κB pathway - Federica Cossu (Elsevier, 2021)
Inhibitors of apoptosis proteins (IAPs) are validated onco-targets, as their overexpression correlates with cancer onset, progression, diffusion and chemoresistance. IAPs regulate cell death survival pathways, inflammation, and immunity. Targeting IAPs, by impairing their protein–protein interaction surfaces, can affect events occurring at different stages of cancer development.To this purpose, we employed a rational virtual screening approach to identify compounds predicted to interfere with the assembly of pro-survival macromolecular complexes. One of the candidates, FC2, was shown to bind in vitro the BIR1 domains of both XIAP and cIAP2. Moreover, we demonstrated that FC2 can induce cancer cell death as a single agent and, more potently, in combination with the Smac-mimetic SM83 or with the cytokine TNF. FC2 determined a prolonged activation of the NF-κB pathway, accompanied to a stabilization of XIAP-TAB1 complex. This candidate molecule represents a valuable lead compound for the development of a new class of IAP-antagonists for cancer treatment.